Prevalence and predictors of the sub-target Hb level in children on dialysis - Stralen, Karlijn J. van; Schaefer, Franz (Nephrology, dialysis, transplantation, 2012)
Abstract: Background. Anaemia is a common and potentially treatable co-morbidity of end-stage renal disease. We aimed to determine the prevalence of the sub-targ